Using the tectophase conceptual model to assess late Triassic–Early Jurassic far-field tectonism across the South-central Barents Sea shelf - Martins, Gustavo; Ettensohn, Frank R.; Knutsen, Stig-Morten (Frontiers in Earth Science, 2024)
The Upper Triassic–Lower Jurassic succession of the Barents Sea Shelf (BSS) represents one of Europe's most prolific and strategic petroleum systems. This succession reflects various depositional environments and tectonostratigraphic events. Even though these strata are considered largely well-understood, connections with far-field stresses triggered by regional tectonics remain a subject of investigation. This study presents new interpretations that focus on relationships between the stratigraphic succession across the south-central BSS and Triassic-Jurassic Novaya Zemlya compressional tectonics. By applying the “tectophase model,” developed in the Appalachian Basin, to analyze this succession, the presence of foreland-basin depozones and associated far-field processes related to compressional tectonics in an adjacent orogen are suggested. This model addresses unconformity development, lithostratigraphic succession, and reactivation of structures. Use of this model suggests far-field tectonostratigraphic responses in two episodes of Novaya Zemlya tectonism, reflected in the coeval BSS stratigraphy. Overall, this tectonostratigraphic study aligns with other research suggesting a Late Triassic inception for Novaya Zemlya compressional tectonism, which influenced larger parts of the BSS through extensive clastic sedimentation, far-field structural reactivation, and flexural responses to deformational loading triggered by tectonics.